Effectiveness of Talent Management Practices in Increasing Job Embeddedness to Reduce Voluntary Turnover Among Malaysian IT Consultants : A Case Study - Ang, Albert Kwan Loong (2014)
Talent retention is becoming an increasingly challenging issue for many organisations worldwide. One of the main reasons is the emergence of the millennial or Gen Y mindset causing talent retention strategies that used to work to no longer have the same effect. Although there has been much literature on talent retention done in the context of the western world, the Malaysian perspective seems to be lacking. Therefore, existing literature was counted upon to guide the development of a sound conceptual framework built around the construct of job embeddedness to induce talent retention. Because of the highly competitive global environment, an organisation that is able to significantly increase productivity and reduce turnover costs through effective talent retention stands to gain a substantial competitive advantage over competitors. The aim of the study was to determine the effectiveness of talent management practices driven by the concept of job embeddedness in reducing voluntary turnover among Malaysian IT Consultants. Data was gathered primarily using a quantitative approach of online questionnaires with an open ended feedback segment for further elaboration. A total of 150 respondents across 40 organisations were engaged in the study. The results were then statistically analysed in order to identify talent management practices with significantly strong influences over job embeddedness. Interestingly, although staffing practices permeates throughout an individual’s entire interaction with the organisation, it was deemed the least significant in fostering job embeddedness. Talent development was discovered to be the strongest influence among millennials while nonmillennials were more inclined to be embedded when working amidst strong leadership. The outcome of the analysis was then used to recommend possible talent management practices that could strategically increase the retention of Malaysian IT Consultants through fostering higher levels of job embeddedness.